Analysis of monthly temperature changes in Iraq to Duration (1950-2021) - Ali, Mustafa (Al-Adab Journal, 2025)
Take up the research is in the direction of change in Minimum, maximum, and average temperature in Iraq for selected climate stations (Mosul, Kirkuk, Baghdad, Rutba, and Basra) For a period of 72 years, between 1950-2021 AD, in which complete temperature data were obtained, and the most prominent results were the clear increase in temperatures as we progressed in time according to the Mann-Kendall regression slope equation. From through a template Makesens- Excel To estimate trends in time series , which was positive in 99% of the months of the year, and it was Parameter results The change in the slope of the slope for the study stations for minimum temperatures is greater than for maximum temperatures, except for the Basra station, and this is consistent with the values ​​of global change, and the Basra station recorded the highest rates of change .At minimum, maximum and average temperatures Increasingly, with strong statistical significance, especially in the summer months, the lowest rates of change were recorded at Baghdad station The results of this research were consistent with the research of other researchers regarding the change in temperature of the stations studied in Iraq.